Parental views on preventing and minimizing negative effects of cyberbullying. (November 2020) - Helfrich, Emily L.; Doty, Jennifer L.; Su, Yi-Wen; Yourell, Jacqlyn L.; Gabrielli, Joy
Highlights: To reduce cyberbullying risk, parents advocated communication and monitoring. Some parents recommended professional resources (e.g., pediatricians, counselors). Promoting perspective and empowerment were suggested communication strategies. Both active and restrictive monitoring are important to prevent cyberbullying. Abstract: Research suggests that victims and perpetrators of cyberbullying are at risk for several psychological problems, including depressive symptoms and suicidal ideation. While cyberbullying among youth most often occurs at home, little research exists on the role of parental involvement in prevention and intervention strategies. The goals of the current study were to (1) identify effective protective strategies that parents use to help youth avoid cyberbullying involvement and (2) identify strategies parents use to build youth's coping capacity when cyberbullying involvement does occur. Researchers conducted seven focus groups, each consisting of two to five participants. Participants were 26 parents (88% female, 69% White) with at least one child in fourth through sixth grade. Results revealed three major conceptual themes: communication, monitoring, and professional resources. Two subthemes of communication emerged: promoting perspective (i.e., helping victims understand how a bully may feel or helping perpetrators understand how their actions affect others) and empowerment (i.e., building confidence in youth to buffer negative effects of cyberbullying on self-esteem). Two subthemes of monitoring emerged: active monitoring (e.g., co-use and discussion of media use) and restrictive monitoring (e.g., limitations and technology control). Findings reinforce the importance of parent involvement in cyberbullying prevention efforts and inform future prevention and intervention program development.